INFLUENCE OF CONSISTENCY AND ACTIVATOR LIQUID ON ACTIVATION PROCESS OF NATURAL ZEOLITE BY HYDROTHERMAL FOR HARDNESS WATER PROCESSING IN FIXED COLUMN - Endang S. Rahayu; Adu Damilsun; Krisna Aditia (Institut Teknologi Bandung, 2010)
Zeolite can function as cation exchanger or adsorbent for elimination pollutan in water. In general, natural zeolite have a low capability to eliminate a hard subtances in water. The study aimed to increase elimination capacity hardness by activated natural zeolite and study the effect of activation processes. This study was conducted to natural zeolite Cikalong-Tasikmalaya with a hydrothermal process at temperature 100 0 C with variations of consistency reaction system, concentration and activator liquid type. Activation natural zeolite was done with variations of consistency of 12,5%; 25%; 37,5%; and 50%, activator liquid concentrate of 2N NaOH and 1N NaOH, and activator liquid types of NaOH and NaCl. The result of process is a active zeolite to the test of implementation a hard water processing in fixed column with depth of zeolites 90 cm, it was operated continously with a linier speed of 2 m/hours, total hardness and hardness of Ca2+ as a parameters test with reference to SNI 06-4161-1996 and SNI 06-2429-1991, variations of standard water concentration between 240 to 440 mg/l as CaCO3. Natural zeolites gave a lower percent between 11% to 42% from variations of standard water concentration which is given, while the zeolite active between 56% to 96%. The effect consistency of activator process is shown in the lowest elimination values of zeolite. The produce of activation process with consistency of 50% and higest value for consistency of 12,5%. Consistency of 12,5 % was used as consistency reference for other variation processes. The effect of activator liquid concentrate NaOH is not siginificant, indicated by narrows range between 2N NaOH and 1N NaOH is 78% to 92%. Activator liquid type NaCl gives a higher hardness percent 96% at standard water with high of hardness.